2006
DOI: 10.2337/diacare.29.03.06.dc05-1992
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Reamputation in Diabetic Patients Stratified by Limb and Level of Amputation

Abstract: OBJECTIVE -This study examined the risk of reamputation, stratified by original level of amputation, in a population of diabetic patients. We also illustrated reamputation rates by ipsilateral and contralateral limbs.RESEARCH DESIGN AND METHODS -The study population included 277 diabetic patients with a first lower-extremity amputation performed between 1993 and 1997 at University Hospital in San Antonio, Texas. Reamputation episodes for the ipsilateral and contralateral limbs were recorded through 2003. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
101
4
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(128 citation statements)
references
References 23 publications
13
101
4
10
Order By: Relevance
“…Age and heel lesions have also been shown to be risk factors for re-amputation (Skoutas et al, 2009). Risk of re-amputation is highest within the first 6 months of initial amputation (Izumi et al, 2006;Skoutas et al, 2009). A re-amputation rate of 21.5% within 18 months was reported by Skoutas et al (2009) and 1 year and 3 year rates of 26.7% and 48.3% by Izumi (2006).…”
Section: Morbidity and Mortality Following Diabetes-related Lower Extmentioning
confidence: 91%
See 1 more Smart Citation
“…Age and heel lesions have also been shown to be risk factors for re-amputation (Skoutas et al, 2009). Risk of re-amputation is highest within the first 6 months of initial amputation (Izumi et al, 2006;Skoutas et al, 2009). A re-amputation rate of 21.5% within 18 months was reported by Skoutas et al (2009) and 1 year and 3 year rates of 26.7% and 48.3% by Izumi (2006).…”
Section: Morbidity and Mortality Following Diabetes-related Lower Extmentioning
confidence: 91%
“…Risk of re-amputation is highest within the first 6 months of initial amputation (Izumi et al, 2006;Skoutas et al, 2009). A re-amputation rate of 21.5% within 18 months was reported by Skoutas et al (2009) and 1 year and 3 year rates of 26.7% and 48.3% by Izumi (2006). Forty percent of subjects with DM in a study by Tentolouris et al had an ipsilateral or contralateral amputation within an average of about 16 months of the first DM-related LEA (Tentolouris et al, 2004).…”
Section: Morbidity and Mortality Following Diabetes-related Lower Extmentioning
confidence: 98%
“…Statistics have shown that, out of the 80,000 amputations performed in the USA per annum, approximately half of these belong to below-knee or more proximal amputations [35]. The estimated 1-year mortality rate after a below-knee amputation ranges between 20.8% and 35.5% [36], with a reported contralateral limb loss rate of 53.3% within 5 years [37]. Research has deduced that proximal amputations result in decreased ambulatory status due to inefficient biomechanics, hence when possible, partial foot amputation is recommended that will reduce morbidity and will help restore biomechanics esp.…”
Section: Discussionmentioning
confidence: 99%
“…Although the actual incidence of bilateral amputation has not been reported, it has been established that 30 to 50 percent of people who have an amputation related to diabetes will undergo amputation of the contralateral limb 3 to 5 yr after the primary amputation [2][3]. Moreover, with the increase in world conflict over the past decade with Operation Iraqi Freedom/Operation Enduring Freedom, coupled with medical advancements and improved emergency medical technician services domestically and abroad, the number of individuals surviving with traumatic bilateral lower-limb amputation (BLLA) has increased [4][5].…”
Section: Introductionmentioning
confidence: 99%